Assessing the performance of social spending in Europe - Antonelli Maria Alessandra; De Bonis Valeria (Central European Journal of Public Policy, 2018)
Based on the construction of a composite index to assess the relative performance of welfare policies, we show that the variability of performances cannot be explained only by the amount of resources devoted to social policies, but also by its composition: countries with higher shares of social public expenditure, specifically aimed at reducing income concentration, obtain better results. This associates the traditional classification of the European welfare systems to the performance obtained in the social sector.